2013
DOI: 10.2141/jpsa.0120013
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: The Effect of Raw and Processed Common Vetch Seed (<i>Vicia sativa</i>) Added to Diets of Laying Hens on Performance, Egg Quality, Blood Parameters and Liver Histopathology

Abstract: Abbreviation Key: C=control diet not containing common vetch seed, CV=common vetch seed. This study was carried out to determine the effects of raw and physical processed common vetch seed added to diets of laying hens on the laying performance, egg quality traits, blood parameters and liver histopathology. Lohman layers, 46 wk of age as 6 replicate cages each containing 4 hens, were allocated randomly to one of four dietary treatments. Treatment groups were fed diets containing a standard commercial layer die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In a further study, the same authors reported that the DFC intake and egg quality of laying hens fed 250 g/kg autoclaved or raw common vetch seeds were similar to those of hens fed a roasted common vetch diet, but the hens exhibited reduced EP. These authors also observed that DFC intake, EP and EW were all reduced in the common vetch treatment groups compared with hens fed a standard commercial layer (control) diet (Kaya et al., ). Conversely, egg quality parameters such as shape index, shell strength, shell thickness, shell weight, yolk colour, yolk index, albumen index and Haugh unit did not differ across treatment groups (Kaya et al., ).…”
Section: Animal Feeding Studies Using Common Vetch Seedsmentioning
confidence: 87%
See 3 more Smart Citations
“…In a further study, the same authors reported that the DFC intake and egg quality of laying hens fed 250 g/kg autoclaved or raw common vetch seeds were similar to those of hens fed a roasted common vetch diet, but the hens exhibited reduced EP. These authors also observed that DFC intake, EP and EW were all reduced in the common vetch treatment groups compared with hens fed a standard commercial layer (control) diet (Kaya et al., ). Conversely, egg quality parameters such as shape index, shell strength, shell thickness, shell weight, yolk colour, yolk index, albumen index and Haugh unit did not differ across treatment groups (Kaya et al., ).…”
Section: Animal Feeding Studies Using Common Vetch Seedsmentioning
confidence: 87%
“…These authors also observed that DFC intake, EP and EW were all reduced in the common vetch treatment groups compared with hens fed a standard commercial layer (control) diet (Kaya et al., ). Conversely, egg quality parameters such as shape index, shell strength, shell thickness, shell weight, yolk colour, yolk index, albumen index and Haugh unit did not differ across treatment groups (Kaya et al., ).…”
Section: Animal Feeding Studies Using Common Vetch Seedsmentioning
confidence: 87%
See 2 more Smart Citations
“…The seed soaking method alone was insufficient to lower 119 GBCA levels as consumption of soaked seed during feeding trials by chickens reduced egg production, 120 daily food consumption and feed conversion ratios were also diminished (Farran et al, 1995). In 121 contrast, boiling the seed produced lower toxin levels such that it could be included in chicken feed at 122 levels of up to 25% without negative effects on growth rates (Kaya et al, 2013). However, consumption 123 This is a provisional file, not the final typeset article of boiled vetch seed that had the broth periodically discarded during boiling resulted in 20% reduced 124 growth rates in chickens when compared with conventional feed with similar protein amounts (Ressler 125 et al, 1997).…”
Section: Limitation Of Gbca Detoxification Using Conventional Methodsmentioning
confidence: 99%